Pengaruh Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using dan Behavior Intention to Use Terhadap Actual System Use dalam Implementasi Teknologi Enterprise Resource Planning (ERP) System (Studi pada End User ERP System di PT Semen Gresik) - Muliati, Niswah (Management Department, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
All dimensions of corporate experience in technology development, therefore the management has to be resourceful and scrupulous to take notice of the latest technological developments as part of efforts to optimize the expected performance and progress. One proof of current information technology advancement is the implementation of Enterprise Resource Planning system (ERP). The results of this research showed an effect of perceived ease of use to perceived usefulness is 72,9% (R 2 = 0,531, t = 12,882) , the perceived ease of use to attitude toward using is 60,1% (R 2 = 0,702, t = 8,927) , the perceived usefulness to attitude toward using is 29,1% (R 2 = 0,702, t = 3,564) , the attitude toward using of behavioral intention to use is 74,1% (R 2 = 0,549, t = 14,778) , and the behavioral intention to use the system to actual system use is 36,2% (R 2 = 0,131, t = 4,603). This research proves that the user acceptance of a technology strongly influenced by perceived ease of use and perceived usefulness which are emerging acceptances and then behavior intention to use where as to reveal the using of a real system in the intensity of usage time